Rapid modeling and 3D matching of GB InSAR landslide emergency monitoring: Method and application - Keli ZHANG; Aimin YAO; Jianquan ZHANG; Yulei YAN; Hongnan QIN (Shuiwen dizhi gongcheng dizhi)
Traditional GB InSAR monitoring relies on surface control coordinates, which can be limiting. To quickly generate a digital elevation model (DEM) at the landslide disaster site, match it with radar deformation images, and achieve three-dimensional visualization of monitoring data, through controlled outdoor simulation experiments, three-dimensional laser scanning technology was used to capture the radar position coordinates during scanning. The position coordinates were integrated into the model’s local coordinate system for direct geometric mapping and three-dimensional matching, which reduces the steps of converting the real coordinates of the measuring radar and instrument coordinates to the real coordinates. Applying this method to a landslide rescue operation in Qinglong, Guizhou can intuitively determine the location of the hazard source, analyze the sliding path, and achieve effective results. The findings indicate that combining 3D laser scanning with geometric mapping matching method enhances rapid modeling and matching at landslide sites, and achieves 3D visualization of radar deformation data. This study facilitates quick location of landslide hazards and analysis of sliding paths and affected areas.